2015
DOI: 10.17979/reipe.2015.0.11.194
|View full text |Cite
|
Sign up to set email alerts
|

La atención temprana en contextos penitenciarios en España

Abstract: ResumenEn España, los hijos de las reclusas pueden residir junto a ellas en centros penitenciarios hasta que alcanzan el tercer año de vida. Esta convivencia garantiza un vínculo afectivo entre el infante y la progenitora pero también sitúa a los niños en un contexto reconocido como factor ambiental de riesgo para su desarrollo. De ahí que nuestro principal objetivo se traduzca en determinar si la Atención Temprana permitiría dar respuesta a sus necesidades psicosocioeducativas. Tras un exhaustivo análisis doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Dimension 4: Enhancing Early Intervention. This includes articles that consider it necessary to broaden the field of action of ECC in two directions: first, towards the prison environment [43], since, although the permanence of the children of prisoners with them until they are three years old is undoubtedly beneficial for the bond of attachment, at the same time it makes them a population of children at risk as a result of the characteristics of the environment about their overall development, and second, possible developmental difficulties in the prenatal period [44], since the maternal-foetal bond occurs before attachment after birth.…”
Section: Analysis Of the Results In Terms Of Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dimension 4: Enhancing Early Intervention. This includes articles that consider it necessary to broaden the field of action of ECC in two directions: first, towards the prison environment [43], since, although the permanence of the children of prisoners with them until they are three years old is undoubtedly beneficial for the bond of attachment, at the same time it makes them a population of children at risk as a result of the characteristics of the environment about their overall development, and second, possible developmental difficulties in the prenatal period [44], since the maternal-foetal bond occurs before attachment after birth.…”
Section: Analysis Of the Results In Terms Of Dimensionsmentioning
confidence: 99%
“…On the other hand, although families are satisfied with the professionals [26] (Balcells-Balcells et al, 2019), a different consideration of needs observed by families and professionals is noted (at least this seems so while analysing the quantities of articles in this scoping review). Parents want early detection [31] (García et al, 2015) to understand what is happening to them (López et al, 2015) [43]. From the professional point of view, the following factors stand out as negative: lack of training [34] (García et al, 2018), lack of intersectoral coordination (Martínez and Calet, 2015) [39], and the need for instruments to perceive the family as an active part (Escorcia et al, 2016) [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation